(untitled) (Palíndromo, 2018)
This paper analyzes the work of the French artist Hubert Duprat, “Trichoptère: la dernière bibliothèque”, prefiguring a library, where the subject covered by the collection is the Tricoptera larvae, and the material available is mostly composed by the collection of the artist. Duprat proposes a work where memory and collection are pierced by art, and the spectator is invited to interact with the collection and its concepts, in a movement where Duprat reinvents his own collection, his way of pre-senting himself to the public as an artist, calling into question the concepts of exhibition, collection and archive. To establish a dialogue with this work, we bring the Chilean artist Alfredo Jaar, whose poetry also permeates the notion of art as archive, as well as an installation of Rosângela Rennó, where we perceive relationships and connections with the works presented, in which we perceive the insertion of the artist by a movement of collecting, where the works have their corporeality rethought and the artist makes us reflect on what are these platforms constitutive of the art.